1971
DOI: 10.1104/pp.47.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Action of Kinetin on Cotyledons of Fenugreek

Abstract: Isolated cotyledons of fenugreek (Trigonella foenum graecum L.), which respond rapidly and specifically to the application of cytokinins with stimulated expansion, have been used to study the primary action of kinetin. Gross chemical analysis showed that ribonucleic acid increased within 24 hours in response to kinetin application. 8-Azaguanine inhibited both kinetin-induced expansion and RNA synthesis; 5-fluorodeoxyuridine inhibited only the RNA synthesis.Cotyledons produced nitrate reductase activity in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The change in RNA synthesis is a time-dependent response to kinetin. This result is similar to both that observed in artichoke tuber tissue (7)(8)(9) where the response is elicited by 2,4-D alone and possibly to cytokinin stimulation of expansion in fenugreek cotyledons where the cytokinin effect required mRNA synthesis (17,18). A similar shift in RNA synthesis was observed during the lag period preceding cell division in a cell line derived from peanut (Arachis hypogea) (28).…”
supporting
confidence: 73%
“…The change in RNA synthesis is a time-dependent response to kinetin. This result is similar to both that observed in artichoke tuber tissue (7)(8)(9) where the response is elicited by 2,4-D alone and possibly to cytokinin stimulation of expansion in fenugreek cotyledons where the cytokinin effect required mRNA synthesis (17,18). A similar shift in RNA synthesis was observed during the lag period preceding cell division in a cell line derived from peanut (Arachis hypogea) (28).…”
supporting
confidence: 73%
“…Rijven and Parkash (11) reported that sucrose increased expansion of kinetin-treated fenugreek cotyledons when incubated in darkness, but (10 x 20 cm). These trays were then enclosed in polyethylene bags and the seed germinated in darkness at 25°C for 38 h. For the experiments, the inner cotyledon from each seedling was excised and placed adaxial surface down on Whatman No.…”
mentioning
confidence: 99%
“…On the other hand, with 8-azaguanine both net RNA synthesis and expansion are inhibited. These together with other observations suggest that kinetin-induced expansion in cotyledons is mediated by the synthesis of mRNA (8).…”
mentioning
confidence: 71%
“…The use of cotyledons has a number of advantages from the point of simplicity in laboratory practice. Also cotyledons exhibiting cytokinin specific responses may be used to investigate the biochemical mechanism of cytokinin action as we report elsewhere (8). Here we describe the expansion of isolated cotyledons as affected by some growth substances, light, nitrogenous compounds, sucrose, and dormancy status.…”
mentioning
confidence: 99%